Choosing Proper Relationship Between Teacher and Students: Interpersonal, Contractual and Pedagogical Relationship - Abun, Damianus; Magallanes, Theogenia (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2018)
Choosing proper relationship is an important matter to be considered particularly in the school setting. Education is intellectual and character and spiritual formation. All kinds of relationship must be tailored toward such aim. The relationship between teachers and students must help the students grow intellectually and spiritually or morally. Based on my presentation, the nature of the relationship between teachers and students must be pedagogical in nature, asymmetrical relationship or between the unequal. The teacher is there to help the students learn and grow intellectually and spiritually.